2018
DOI: 10.3892/etm.2018.6190
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of acupuncture with MOK, a polyherbal medicine, on PTU‑induced hypothyroidism in rats

Abstract: Acupuncture with MOK, a polyherbal medicine (MOK pharmacopuncture), has been used for the treatment of thyroid syndromes including hypothyroidism and hyperthyroidism in traditional Korean medicine. The present study investigated the effect of MOK pharmacopuncture on hypothyroidism and the mechanism underlying its antioxidation and immune regulation effects. Hypothyroidism was induced in Sprague-Dawley rats by subcutaneous injection of Propylthiouracil (PTU; 10 mg/kg) once daily for 4 weeks. MOK was administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 43 publications
5
22
1
Order By: Relevance
“…Specifically, MOK has been reported to exert anti-inflammatory effects in cell-based assays ( 14 ). Moreover, its in vivo anti-hypothyroidism and anti-hyperthyroidism effects have been confirmed in previous studies ( 15 , 16 ). In addition, its inhibitory function on the production of inflammatory mediators by primary peritoneal macrophages has been reported ( 17 ).…”
Section: Introductionsupporting
confidence: 76%
“…Specifically, MOK has been reported to exert anti-inflammatory effects in cell-based assays ( 14 ). Moreover, its in vivo anti-hypothyroidism and anti-hyperthyroidism effects have been confirmed in previous studies ( 15 , 16 ). In addition, its inhibitory function on the production of inflammatory mediators by primary peritoneal macrophages has been reported ( 17 ).…”
Section: Introductionsupporting
confidence: 76%
“…Quantification of morphometric changes of thyroid follicular cell height, thyroid epithelium thickness and hepatocytes count has been performed by ImageJ NIH analysis software, as done earlier by Hwang et al . 62 .…”
Section: Methodsmentioning
confidence: 99%
“…As discussed earlier, a large number of previous studies had reported the efficacy of Ayurvedic and herbal remedies against hypothyroidism. [8][9][10][11][12][13][14]…”
Section: Review Resultsmentioning
confidence: 99%
“…Several herbal remedies have been found mentioned in the ancient science of traditional medicines, including Ayurveda that was found to have shown an increase in both serum T3 and serum T4. [8][9][10][11][12][13][14] Although there is no direct mention of the thyroid gland in Ayurveda, the physiological and biochemical functions of the thyroid hormone can be compared with the description of Agni (digestive power maintaining body metabolism). There is also mention of a disease called Galaganda that Charaka mentions among 20 varieties of Kaphaja diseases as a solitary swelling in the neck.…”
Section: Introductionmentioning
confidence: 99%